Effects of different supplemental soya bean oil levels on the performance of prepubertal Saanen goats: Oestrogen and progesterone release. Issue 6 (22nd February 2016) - Bomfim, G. F.; Merighe, G. K. F.; de Oliveira, S. A.; Rodrigues, A. D.; Augusto, L.; Teixeira, I. A. M. A.; de Resende, K. T.; Negrao, J. A.
Summary: The aim of this study was to investigate the effects of different levels of soya bean oil in the total diet on the growth rate, metabolic changes, and oestrogen and progesterone release in Saanen goats. After dietary adaptation, 21 prepubertal goats (weight of 29.12 ± 0.91 kg, 230 days old) were randomly distributed among three diets of D2: inclusion of 2% soya bean oil in the total diet; D3: basal diet – inclusion of 3% soya bean oil in the total diet; and D4: inclusion of 4% soya bean oil in the total diet. The basal diet (D3) was formulated to promote a daily gain of 0.140 kg. The goats were weighed, and their blood samples were collected weekly. Glucose, cholesterol, triglycerides, total protein, urea, non‐esterified fatty acids, beta‐hydroxybutyrate, oestrogen and progesterone in the plasma were measured. Prepubertal goats that were fed D4 exhibited a significantly lower dry matter intake, urea and cholesterol levels compared with the goats that were fed D2 and D3. Indeed, goats that were fed D4 displayed a significantly lower final weight than goats that were fed D2 and D3. In contrast, the inclusion of soya bean oil in the diet increased the progesterone and oestrogen concentrations, and goats that were fed D4 released a significantly higher concentration of progesterone than those that were fed D2 and D3. Furthermore, the percentage of goats with a progesterone level greater than 1 ng/ml (functional Corpus luteum ) was significantly higher among the goats that were fed D3 and D4 than among those that were fed D2. In this study, although the inclusion of 4% soya bean oil in the diet decreased dry matter intake and growth rate, it increased progesterone concentration and the percentage of goats with a functional Corpus luteum, suggesting that the inclusion of soya bean oil accelerated puberty in prepubertal goats.